The incredible journey of Lewis and Clark - Blumberg, Rhoda (New York : Lothrop, Lee & Shepard Books, 1987)
Describes the expedition led by Lewis and Clark to explore the unknown western regions of America at the beginning of the nineteenth century.
Includes index.
Bibliography: p. 139.
Keywords: Lewis, Meriwether, -- 1774-1809 -- Juvenile literature; Clark, William, -- 1770-1838 -- Juvenile literature; Lewis, Meriwether, -- 1774-1809.; Clark, William, -- 1770-1838.; Explorers; West (U.S.) -- Description and travel -- Juvenile literature; West (U.S.) -- History -- To 1848 -- Juvenile literature; West (U.S.) -- Discovery and exploration